Fast-Track Anesthesia for Cito Craniotomy Evacuation Hematoma Due to Temporoparietal Subdural Hemorrhagic Hematoma in a Pediatric Patient: A Case Report - Wardhana, Anggia Rarasati; Ardana Tri Arianto (HM Publisher, 2024)
Introduction: Subdural hematoma (SDH) in early childhood is a serious condition that requires immediate surgical intervention. Fast-track anesthesia is an approach that aims to speed up the patient's recovery after surgery. This case report presents the experience of fast-track anesthesia in a 4-month-old pediatric patient with SDH who underwent a cito craniotomy. Case presentation: A 4-month-old child with a history of head trauma due to shaking experienced recurrent seizures. CT scan examination showed left temporoparietal SDH with intraparenchymal hemorrhage. The patient was classified as ASA IIIE and underwent a cito craniotomy. A fast-track anesthesia strategy was implemented using rapid induction, multimodal analgesia, and strict fluid management. Conclusion: Fast-track anesthesia was successfully applied to pediatric patients with SDH undergoing cito craniotomy. This approach allows for a quicker recovery, reduces postoperative complications, and shortens the length of hospital stay.